Analisis Pengaruh Tingkat Nisbah Bagi Hasil, Pelayanan, dan Produk Terhadap Kepuasan Nasabah Tabungan Pada Bank Syariah Mandiri XXX - Meilinda Eko Yahyanti (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2019)
The purpose of this study is to determine the effect of ratios, services, products on customer satisfaction BSM savings at Bank Syariah Mandiri XXX. This study is quantitative with a total of 100 data were collected using survey method random sampling technique. The result study indicate that simultaneously the ratio, service, and product variables have a positive and significant influence on the satisfaction of BSM savings customers with a coefficient of 93.778. While partially the effect is different, the ratio variable has a positive and significant effect on the satisfaction of BSM savings customers with a coefficient of 5.092, the product variable has a positive and significant influence on the satisfaction of BSM savings customers with a coefficient of 8.780, while the service variable has no significant effect on customer satisfaction BSM savings with a coefficient of 0.597. The conclusion of this study shows that the regression model that is formed with the ratio, service, and product variables can be used to see the effect of BSM savings customer satisfaction.